Combination of Nitrogen and Potassium Improve Radiation Use Efficiency, Growth, Yield, and Agronomic Efficiency in Maize Cultivation - Azizah, Nur; Nihayati, Ellis; Widaryanto, Eko; Sugito, Yogi (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2025)
Proper management of nitrogen (N) and potassium (K) is needed to increase maize productivity in the area having low soil fertility due to their crucial role for plant growth and production. The research aimed to analyze the effect of N and K fertilizer doses on growth, production, radiation use and agronomic efficiencies during two years maize cultivation. The research was carried out on March to July 2021 and January to May 2022 in Jatikerto Agro Techno Park, Malang - East Java, Indonesia. The experiment used 16 treatment combinations of nitrogen (0, 38, 77, and 115 kg N/ha in 2021 and 0, 50, 100, 150 kg N ha-1 in 2022) and potassium (0, 33, 67, and 100 kg K ha-1 in 2021 and 0, 50, 100, and 150 kg K ha-1 in 2022) fertilizer rates, and repeated three times of each. Maize growth and production (such as plant height, leaf number, leaf area index, interception photosynthetically active radiation, radiation use efficiency, yield) were significantly increased by application 77 and 150 kg N ha-1 combined with 67 and 150 kg K ha-1. The study found strongly effect of leaf area index and radiation use efficiency in increasing grain yield of maize (R2 = 0.94 and 0.98, respectively). However, the increases fertilizer rates should be anticipated their negative effect on agronomic efficiency. Therefore, proper combination of N and K should be considered to obtain the optimum maize growth and production, as well as maintain radiation use and agronomic efficiencies.